EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN PEDIATRI RAWAT INAP DI RUMAH SAKIT UMUM GANESHA - Ni Kadek Putri Dwiyanti (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
The use of antibiotics in pediatric patients is often inappropriate and risks causing resistance, prolonging the hospitalization, and effectiveness decreasing. Pediatrics are a group that requires more attention in antibiotic therapy due to the differences in pharmacokinetics and pharmacodynamics compared to adults. This study aims to evaluate the pattern, quality, and quantity of antibiotic use in pediatric patients at Ganesha General Hospital for the period October–December 2024, and relationship between the quality of antibiotic use and the length of hospitalization. The research design is descriptive-analytic retrospective with a quantitative approach. The evaluation of the quality of antibiotic use using Gyssens method, while the quantity using ATC/DDD and DU90% methods. The data were analyzed univariate and bivariate using Chi-Square test. The results on 97 patients showed that cephriaxone was the most used antibiotic (80.8%) with DDD/100 patient value of 51.28. The quality showed 83.51% of antibiotic use was rational (category 0), 16.49% were in category VI (incomplete data) of 7.22%. The results of Chi-Square test showed there was no significant relationship between the quality of antibiotic use and the length of hospitalization (p = 0.410). The conclusion is that there is still a high level of irrational use of antibiotics.